2011
DOI: 10.1083/jcb.201009126
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase signaling pathway mediated by p110α regulates invadopodia formation

Abstract: Inhibition of p110α or of the downstream PI3K signaling pathway components PDK1 and Akt, as well as phosphoinositide sequestration, blocks invadopodia formation in breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 67 publications
7
116
3
Order By: Relevance
“…Formation of invadopodia in cancer cells or podosomes in Srctransformed fibroblasts requires activation of Smads and PI3K (76)(77)(78)(79). In this work, we showed that pharmacological inhibition of PI3K blocked invadosome-mediated ECM degradation in RA synoviocytes or in cells stimulated with PDGF.…”
Section: Discussionmentioning
confidence: 53%
“…Formation of invadopodia in cancer cells or podosomes in Srctransformed fibroblasts requires activation of Smads and PI3K (76)(77)(78)(79). In this work, we showed that pharmacological inhibition of PI3K blocked invadosome-mediated ECM degradation in RA synoviocytes or in cells stimulated with PDGF.…”
Section: Discussionmentioning
confidence: 53%
“…S4D) is unique to this mutation. Interestingly, increased PI(3,4)P 2 levels are thought to promote increased cell migration (22)(23)(24). Given these findings and our mass spectrometry data showing enrichment of cell migration processes, we hypothesized that the increased PI(3,4)P 2 levels in p.A126G would cause increased cell migration relative to PTEN loss-of-function mutations.…”
Section: Significancementioning
confidence: 83%
“…There is a statistical significance between mutant p.A126G and catalytic dead p. find that this changed enzymatic specificity causes an oncogenic increase in PI(3,4)P 2 levels at the expense of the PI(3,4,5)P 3 concentration. Up-regulation of PI(3,4)P 2 is typically associated with increased cell migration (23,24), and we are able to demonstrate, through global phospho-proteome characterization and in vitro cellular assays, that PTEN p.A126G interferes with cell proliferation pathways and likely even increases the ability of cells to migrate. Contrary to current dogma, these observations suggest that PTEN can also act as an oncogene as well as a tumor suppressor.…”
Section: Significancementioning
confidence: 86%
“…Immunofluorescence was conducted as previously described (34). Briefly, the cells were fixed in 4% paraformaldehyde for 15 minutes and permeabilized with 0.1% Triton X-100 for 5 minutes.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Fluorescent gelatin-coated coverslips were prepared as described previously (29,34). MDA-MB-231 and RPMI 7951 cells were cultured for 3 to 7 hours on coverslips coated with fluorescent gelatin.…”
Section: Invadopodia Assaymentioning
confidence: 99%